Anticancer properties of phospholipase A2 from Daboia siamensis venom on human skin melanoma cells. Issue 1 (December 2016) - Khunsap, Suchitra; Khow, Orawan; Buranapraditkun, Supranee; Suntrarachun, Sunutcha; Puthong, Songchan; Boonchang, Supatsorn
Abstract Background Phospholipase A2 (PLA2 ) is a major component of theDaboia siamensis venom, which is able to hydrolyse the membrane of various cells. For this reason, the activity of PLA2 was investigated regarding its pharmaceutical properties. This study was conducted to explore the pharmacological properties of a PLA2 fromDaboia siamensis (dssPLA2 ) venom on human skin melanoma cell line (SK-MEL-28). Methods dssPLA2 was isolated by ion exchange and gel filtration columns. Various concentrations of dssPLA2 were investigated for cytotoxic activity and inhibition of migration on SK-MEL-28 cells. Cell death analysis, mRNA expression levels of Notch I-III and BRAF V600E genes were also determined. Results dssPLA2 exhibited cytotoxicity on SK-MEL-28 for 24 and 72 h as compared with untreated cells. However, it had no toxic effects on CCD-1064sk cells under the same conditions. dssPLA2 (0.25 and 0.5 μg/mL) induced 17.16 and 30.60 % of apoptosis, while activated 6.53 and 7.05 % of necrotic cells. dssPLA2 at 0.25, 0.5, 1 and 2 μg/mL could inhibit migration on SK-MEL-28 cells for 24 h by 31.06, 41.66, 50 and 68.75 %, respectively. The action of dssPLA2 significantly reduced the levels of Notch I and BRAF V600E genes expression on SK-MEL-28 cells compared with untreated cells at 72 h. Conclusions This study indicates that dssPLA2 had potential effects of apoptosis, necrosis, cytotoxicity and inhibition of migration on SK-MEL-28 cells. dssPLA2 could possibly be a selective agent that targets cancer cells without affecting normal cells.